New frontiers in nanochemistry : concepts, theories, and trends. Volume 3, Sustainable nanochemistry - Putz, Mihai V. (Palm Bay, Florida : Apple Academic Press, 2014)
The final volume of this new innovative and informative three-volume set explains and explores the essential basic and advanced concepts from various areas within the nanosciences. This volume primarily focuses on increasing awareness of sustainable nanochemistry, meaning the social and economic impact of nanochemistry, in order to mitigate ecological resource depletion and to promote the exploration of nature as a resource for future benefits. This volume adopts a pharmacological lens, examining the multitude of ways in which nano-research can contribute to the development of pharmaceutical drugs and paying particular attention to toxicology and renewable energy within nanochemistry. Under the vast expertise of the editor, the volume contains 34 entries contributed by renowned international scientists and scholars. The content in this volume covers topics such as anti-HIV agents, ecotoxicology, solar cells and photovoltaic phenomena, spectral-SAR, and moreálphabetically organized and accompanied by equations, figures, and brief letters in order to emphasize the potential applications of the concepts discussed.
OCLC-licensed vendor bibliographic record.
Keywords: Nanochemistry; Nanostructured materials